1999
DOI: 10.1080/1361332990020203
|View full text |Cite
|
Sign up to set email alerts
|

Judgements on Justice: young people and Aboriginal reconciliation

Abstract: Aboriginal reconciliation is a process intended to address indigenous disadvantage through education and the promotion of a wider understanding of the unique position of indigenous Australians. The emergence in Queensland of an extremist, right wing political force, explicitly antagonistic to issues fundamental to the process of reconciliation, has alarmed educators and teachers. While a good deal of attention has focused on the views of adults, little is known about those of young people. Based on research un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…However, prevailing biased narratives, as well as direct experience, clearly influence young people. For instance, a study of Australian primary students’ understandings of the possibilities for inter-group reconciliation with aboriginal people found that, “Racialisation was the prism through which students understood and experienced others’ and their own social and political position” (Aberdeen and Mariko Matthews, 1999: 215). Although the children expressed abstract beliefs in tolerance, equality, and justice, these beliefs coexisted with inaccurate, ethnocentric ideas.…”
Section: Young People’s Understandings Of Social Conflict and The Potmentioning
confidence: 99%
“…However, prevailing biased narratives, as well as direct experience, clearly influence young people. For instance, a study of Australian primary students’ understandings of the possibilities for inter-group reconciliation with aboriginal people found that, “Racialisation was the prism through which students understood and experienced others’ and their own social and political position” (Aberdeen and Mariko Matthews, 1999: 215). Although the children expressed abstract beliefs in tolerance, equality, and justice, these beliefs coexisted with inaccurate, ethnocentric ideas.…”
Section: Young People’s Understandings Of Social Conflict and The Potmentioning
confidence: 99%
“…It aimed to address Indigenous disadvantage through community education and the provision of advice to government and other agencies (Aberdeen & Matthews, 1999, Hollinsworth, 1998. The main role of reconciliation was, To bring about through education, a greater level of awareness of Aboriginal History, cultures, dispossession, continuing disadvantage and the need to redress disadvantage.…”
Section: Contemporary Novelists Such Alexander Mccall Smith and His Smentioning
confidence: 99%